PENGARUH GAYA KEPEMIMPINAN OTORITER, GAJI DAN INSENTIF TERHADAP KINERJA KARYAWAN PADA CV. SURYA ART GLASS KABUPATEN KEDIRI - Ade Dwi Julianto; Rafikhein Novia Ayuanti (Commodities, Journal of Economic and Business, 2024)
The competition among companies in the era of globalization is increasingly intense in both the trade and service industries. Therefore, companies need to improve their performance in all areas. It has been proven that companies that survive are those with reliable human resources and good performance. The aim of this study is to examine the influence of authoritarian leadership style (X1), salary (X2), and incentives (X3) on employee performance (Y) at CV. Surya Art Glass Kediri. The sample size in this study is 55 people, consisting of all employees of CV. Surya Art Glass in Kediri Regency. The sampling technique used in this study is saturated sampling. Data analysis in this study utilizes Validity Test, Reliability Test, Multiple Linear Regression Test, including t-test and f-test. The results of this study indicate that the variables of Authoritarian Leadership Style, Salary, and Incentives have a positive and significant effect on the Employee Performance variable. From the t-test results, the Authoritarian Leadership Style variable has a value of 0.003, which is less than 0.05, indicating that the Authoritarian Leadership Style variable has a positive and significant effect on employee performance. The Salary variable has a result of 0.033, which is less than 0.05, making it positive and significant. The Incentives variable has a result of 0.003, which is less than 0.05, making it positive and significant. The F-test results show that the calculated F is 7.629 with a sig. F value of 0.001 < 0.05, indicating that Authoritarian Leadership Style, Salary, and Incentives together have a significant effect on the employee performance variable.